2011
DOI: 10.2478/v10183-011-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Soil development and soil biology on King George Island, Maritime Antarctic

Abstract: Abstract:This review covers aspects of soil science and soil biology of Antarctica with special focus on King George Island, South Shetlands, the martitime Antarctic. New approaches in soil descriptions and soil taxonomy show a great variety of soil types, related to different parent material, mainly volcanic origin, as well as on influences by soil biological processes. The spread of higher rooting plants attract microorganisms, nematodes and collemboles which in turn build new organic material and change the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 50 publications
2
28
0
2
Order By: Relevance
“…The marked difference between the acidic soils on platforms and the alkaline soils on moraines correspond to the more recent exposure of the latter that preserve most the characteristics of the parent material as the close link with carbonates in the depth profiles of soils on moraines also suggests. These patterns coincide with the geographical distribution of alkaline pH values linked to that of parent material found in the proximity to glaciers and tending to acidification towards the coast, where fauna activity increases producing strong acids by the mineralization of guano (Tatur & Barczuk, ) and soil processes had been acting longer (Bölter, ; Bölter, Blume, Schneider, & Beyer, ; Navas et al, ; Wilhelm, Bockheim, & Haus, ).…”
Section: Discussionsupporting
confidence: 60%
“…The marked difference between the acidic soils on platforms and the alkaline soils on moraines correspond to the more recent exposure of the latter that preserve most the characteristics of the parent material as the close link with carbonates in the depth profiles of soils on moraines also suggests. These patterns coincide with the geographical distribution of alkaline pH values linked to that of parent material found in the proximity to glaciers and tending to acidification towards the coast, where fauna activity increases producing strong acids by the mineralization of guano (Tatur & Barczuk, ) and soil processes had been acting longer (Bölter, ; Bölter, Blume, Schneider, & Beyer, ; Navas et al, ; Wilhelm, Bockheim, & Haus, ).…”
Section: Discussionsupporting
confidence: 60%
“…However, Chacon et al (2013) showed that the less extreme microclimatic conditions and the presence of liquid water in the ice-free area promote the biogeochemical cycling of soil P. Soils of the area contain secondary minerals, such as haematite and the intergrade chlorite-vermiculite-montmorillonite. Similarly, N in these soils usually has the form of a salt (Bolter 2011). As demonstrated by Green et al (2005), a comparatively low NO 3 - /Cl - ratio (0.003–0.018) indicates that atmospheric precipitation may be the source of N.…”
Section: Discussionmentioning
confidence: 99%
“…The most investigated area in West Antarctica in terms of pedological alterations of the solum is King George Island, particularly the Fildes Peninsula. The soil diversity and genesis have been described in relation to environmental conditions (Bolter 2001), and the soils of King George Island are considered to be the most developed in the whole of the Antarctic Peninsula (Simas et al . 2015).…”
Section: Introductionmentioning
confidence: 99%